Measurement of CFHT Images I: Identification, Photometry and Classification - Calderon, Jesus Humberto (2014)
In this paper we present preliminary results from the measurement and analysis of imag es of the ecliptic zoneobtained with MegaCam at Canada-France-Hawaii Telescope (CFHT) located a t Mauna Kea(Hawaii ). We areevaluating the feasibili ty of constructing an astrometric and photometric cataloguewith all the a stronomicalsources identified on those imag es. We comm ent and discuss the criteria a nd procedures for the identificationof sources, the photometric reduction and their class ification as s tellar or extendedobjects